Expansion of Vero cells on low-cost ultraviolet/ozone (UVO) treated polystyrene (PS) microcarriers for Newcastle disease virus(NDV) production - Arifin, Mohd Azmir; Nurhusna, Samsudin (2020)
Newcastle disease (ND) caused by Newcastle disease virus (NDV) is regarded as one of the most important poultry diseases in the world. ND vaccines until now is mainly produced by growing NDV vaccine strains in embryonated chicken eggs. This method poses many drawbacks, such as poor-quality control, high labor-intensity, time-consuming and requires big area for egg incubation. One method that has high possibility to overcome all the problems mentioned is by producing ND vaccines using animal cell culture. Animal cell culture offers many advantages over the traditional chicken eggs method. The method is rapid, convenient, less expensive than eggs, supports easy scale up and it allows evidence of viral proliferation to be examined microscopically. Further, with the advent of microcarrier cell culture technology, high density cell culture is achievable and virus yield produced from the cell culture is expected to be more than the embryonated chicken eggs method or at least on par. The present work aims to prepare a model to mass produce mesogenic La Sota strain of NDV using self-prepared ultraviolet/ozone (UVO) treated polystyrene (PS) microcarriers in spinner vessel culture. First, Vero cell culture were sequentially adapted from using Dulbecco’s Modification of Eagle Medium (DMEM) to Virus-Production Serum Free Medium (VP-SFM). Adapted Vero cells were later used as hosts to propagate La Sota NDV in T-flask cultures. Concurrently, PS microspheres were produced using oil in water (O/W) emulsification-solvent evaporation method, and then treated with UVO to introduce functional groups that can promote cell adherence and growth. UVO treated PS microcarriers were characterized by toluidine blue O (TBO) assay, Fourier-transformed infra-red (FTIR) and scanning electron microscopy (SEM). From experiments, it was revealed that, adaptation from 100% DMEM to culture in 100% VP-SFM has resulted higher maximum cell concentration, from 1.063 × 106 cells/ml to 1.595 × 106 cells/ml, respectively. However, La Sota propagation in Vero cells that were cultured in 100% VP-SFM yielded 0 HA titer for 5 consecutive adaptations. On the other hand, analysis of UVO treated by PS microcarriers by TBO assay and FTIR showed increased surface oxygen concentration after UVO treatment. Results from spinner flask culture also revealed that UVO treated PS microspheres support the growth of Vero cells to high cell density.